On the regularity of solutions to the Beltrami equation in the Plane. Issue 2 (1st February 2019) - Veetel, Bindu K.
ABSTRACT: We obtain interior estimates on regularity of solutions to the inhomogeneous Beltrami equation in the plane, namely∂ ¯ f - μ ∂ f - ν ∂ f ¯ = h when h and the coefficientsμ andν are Dini continuous; the coefficients satisfy an ellipticity condition| μ ( z ) | + | ν ( z ) | ≤ κ < 1 .